Entre o Acesso e a Proteção - Um Estudo sobre Verificação de Idade e Segurança Infantil em Plataformas Digitais - Theodoro, André de Andrade; Valença, George (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
Given the ease of unsupervised access and growing risks for minors online, safeguarding children’s digital rights is increasingly urgent. As personal data becomes a major economic asset, governments are enforcing stricter age verification rules. This study examines age verification designs on the most-used social media platforms by Brazilian children and adolescents. In the first phase, we created test accounts and analyzed the terms of use on YouTube, TikTok, Instagram, and WhatsApp. In the second, we analyzed responses to a public consultation by the Brazilian Internet Steering Committee to identify concerns related to this topic. Findings show that platforms in Brazil mirror those in the EU, with easily bypassed age checks. The results call for a redesign of current mechanisms to ensure safer, more ethical digital experiences for children.